Does health insurance impede trade in health care services? - Mattoo, Aaditya, 1961- 1961- (Policy research working paper, 2005)
"There is limited trade in health services despite big differences in the price of health care across countries. Whether patients travel abroad for health care depends on the coverage of treatments by their health insurance plan. Under existing health insurance contracts, the gains from trade are not fully internalized by the consumer. The result is a strong "local-market bias" in the consumption of health care. A simple modification of existing insurance products can create sufficient incentives for consumers to travel. For just 15 highly tradable, low-risk treatments, the annual savings to the United States would be